Negras Raízes: Fé, Liberdade e resistencia na irmandade de São Benedito em meados do século XIX em São Paulo - Miranda, Eliana da Silva (2006)
This work purpose is to display The Glorious Brotherhood of Saint Benedict in The middle of the nineteenth century. It intends to showcase the black religiosity, based on a large number of myths, beliefs and fears, in a period the black were seen as an exchange good. Thus, this research tries to recover a story which has begun to be told. Furthermore, upon the study of other authors on different brotherhoods. The Brotherhood of Saint Benedict is believed to have been a homogenous institution. Despite the theme complexity and the material lackness, such as newspapers, periodics. Internet sites and books, this case study can spotlignt an original and unpublished subject